Cache replacement positions in information-centric network - Che Mohamed Arif, Ahmad Suki; Hassan, Suhaidi; Abdullahi, Ibrahim (2015)
Information dissemination as the sole functionality driving the current Internet trend has been of keen interest for its manageability. Information Centric Network (ICN) proposed as a new paradigm shift to mitigate the predicted traffic of the current Internet.However, caching as an advantageous building block of ICN is faced with the challenges of content placement, content replacement and eviction.The current practice of ICN caching has given birth to the problems of content redundancy, path redundancy and excessive wastage of bandwidth.This study analyzes the intelligence in cache content management to palliate the gross expenses incurred in the ICN practice.The use of the current factors in previous studies in recency and frequency in content usage play delicate roles in our study. Replacement strategies are agreed to influence the entire cache-hit, stretch and Network diversity.